2019
DOI: 10.1111/mve.12379
|View full text |Cite
|
Sign up to set email alerts
|

Latitudinal diversity of biting midge species within the Obsoletus group across three habitats in Europe

Abstract: Culicoides species from the Obsoletus group are important vectors of bluetongue and Schmallenberg virus. This group consists of several species that cannot easily be identified using morphological characteristics. Therefore, limited information is available about their distribution and habitat preferences. In this study, we aimed to elucidate the species composition of the Obsoletus group in three habitat types at climatically different latitudes across Europe. Traps were placed in three habitat types in three… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 28 publications
2
2
0
Order By: Relevance
“…Species assignment at the European scale showed variation in the distribution of the cryptic diversity of Obsoletus/Scoticus Complex. This result confirmed a previous study by Möhlmann et al [49], who found a strong latitudinal effect on the relative abundance of species of the Obsoletus/Scoticus Complex. However, the previous study was carried out with few individuals from a relatively small number of countries and sampling sites [49].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Species assignment at the European scale showed variation in the distribution of the cryptic diversity of Obsoletus/Scoticus Complex. This result confirmed a previous study by Möhlmann et al [49], who found a strong latitudinal effect on the relative abundance of species of the Obsoletus/Scoticus Complex. However, the previous study was carried out with few individuals from a relatively small number of countries and sampling sites [49].…”
Section: Discussionsupporting
confidence: 93%
“…This result confirmed a previous study by Möhlmann et al [49], who found a strong latitudinal effect on the relative abundance of species of the Obsoletus/Scoticus Complex. However, the previous study was carried out with few individuals from a relatively small number of countries and sampling sites [49]. This contrasts with our study, the first to be conducted at a European scale with a large data set sufficient to provide a more precise idea of the cryptic diversity within the Obsoletus/Scoticus Complex.…”
Section: Discussionsupporting
confidence: 93%
“…After identification of the species in the Obsoletus group, five abdomens per species were pooled in a 2-ml screw-cap microtube (Sarstedt) with a 4-mm borosilicate glass bead (Sigma-Aldrich). As expected, the four species of the Obsoletus group were not present in all the studied countries [38]. Therefore, a total of 20 pools were made for Sweden (1 × C. dewulfi, 5 × C. obsoletus s.s., 14 × C. scoticus), 37 pools for The Netherlands (3 × C. chiopterus, 12 × C. dewulfi, 11 × C. obsoletus s.s., 11 × C. scoticus) and 18 pools for Italy (9 × C. obsoletus s.s., 9 × C. scoticus) (Table 1).…”
Section: Field-collected Biting Midgesmentioning
confidence: 76%
“…For molecular identification, DNA was extracted using a Chelex-based extraction method [ 37 , 38 ]. First, 30 µl of 5% Chelex® 100 resin (143–2832 BioRad) in ultrapure water was added to each sample in the 96-well plate.…”
Section: Methodsmentioning
confidence: 99%